2017
DOI: 10.18632/oncotarget.19626
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor mediates TGF-β1-induced low-grade serous ovarian tumor cell apoptosis

Abstract: Ovarian low-grade serous carcinoma (LGSC) is a rare disease and is now considered to be a distinct entity from high-grade serous carcinoma (HGSC), which is the most common and malignant form of epithelial ovarian cancer. Connective tissue growth factor (CTGF) is a secreted matricellular protein that has been shown to modulate many biological functions by interacting with multiple molecules in the microenvironment. Increasing evidence indicates that aberrant expression of CTGF is associated with cancer developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…19 Interestingly, smad3 signalling mediates TGFβ1-induced CTGF expression and is essential for the pathogenesis of cardiac remodelling. 44,45 In the present study, given that decorin levels were high in severe HF patients compared with controls and decreased following HT, a decrease that was associated with improvement in MRAP, LVSWI, and NT-proBNP, it is reasonable to hypothesize that higher levels of plasma decorin may have a cardioprotective role in HF by inhibiting the profibrotic activity of TGFβ and its effector CTGF, possibly in a smad3-dependent manner, attenuating adverse cardiac remodelling.…”
Section: Discussionmentioning
confidence: 70%
“…19 Interestingly, smad3 signalling mediates TGFβ1-induced CTGF expression and is essential for the pathogenesis of cardiac remodelling. 44,45 In the present study, given that decorin levels were high in severe HF patients compared with controls and decreased following HT, a decrease that was associated with improvement in MRAP, LVSWI, and NT-proBNP, it is reasonable to hypothesize that higher levels of plasma decorin may have a cardioprotective role in HF by inhibiting the profibrotic activity of TGFβ and its effector CTGF, possibly in a smad3-dependent manner, attenuating adverse cardiac remodelling.…”
Section: Discussionmentioning
confidence: 70%
“…It was reported that CTGF could positively mediate apoptosis in ovarian low-grade serous carcinoma and MCF-7, a breast cancer cell line 120 , 121 . However, in human Tenon capsule fibroblasts and chicken embryo fibroblasts, CTGF was found to negatively mediate the apoptosis 122 , 123 .…”
Section: Regulation Of Cellular Events By Ctgfmentioning
confidence: 99%
“…Transforming growth factor beta (TGF-β) plays an important role in promoting cell proliferation and cell cycle regulation in early oncogenesis and normal tissue development [10, 11]. Previous studies have found that TGF-β1 can activate both SMAD2 and SMAD3 [12]. SMAD2 and 3 dimerize, forming the SMAD2/3 complex.…”
Section: Introductionmentioning
confidence: 99%